The Influence of the Giving Question and Getting Answer Learning Model on the Learning Activity of Class IV Students in the PKN Subject at MI Mathlaul Anwar - Azwar Anas; Siva Fauziah (al-Afkar, Journal For Islamic Studies, 2024)
The problem in this study is the lack of student learning activity at MI Mathlaul Anwar. The purpose of this study is to describe the steps of the learning model of Giving Questions and Getting Answers, increasing student learning activities, and increasing learning activities in PKN subjects. This research uses descriptive quantitative research. The sampling technique used is the saturated sampling technique. The subjects of this study were fourth grade students totaling 81 students. The data collection technique used is a questionnaire. Based on the results of the study, it can be concluded that the value of the correlation coefficient of the variables X and Y obtained from tcount is 15.248 which is greater at a significant level of 5%, then Ho is rejected and Ha is accepted. The result of the coefficient of determination is 0.746 or 74.6%, which means that the Giving Question and Getting Answer learning model has an influence of 74.6% on student activity. The results showed that the Giving Question and Getting Answer learning model had an effect on students' active learning in Civics subjects.